First, let's find the slope (m) of the line using the two points:
m = (y2 - y1) / (x2 - x1)
m = (3 - 2) / (0 - 2)
m = 1 / -2
m = -1/2
Now that we have the slope, we can use the point-slope form of the equation of a line:
y - y1 = m(x - x1)
Using the first point (2, 2):
y - 2 = -1/2(x - 2)
y - 2 = -1/2x + 1
y = -1/2x + 3
Therefore, the equation of the linear function that passes through the points (2, 2) and (0,3) is:
y = -1/2x + 3
Write the equation of the linear function that passes through the points (2,2) and (0,3)
y = __ x + __
1 answer